2018
DOI: 10.1111/lam.12890
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial and marine Antarctic fungi extracts active against Xanthomonas citri subsp. citri

Abstract: This manuscript makes an impact on the study of micro-organisms from extreme habitats and their possible contribution in discovering new active molecules against pathogens of agricultural interest. Studies on the Antarctic continent and its communities have attracted the scientific community due to the long period of isolation and low levels of disturbance that surrounds the region. Knowing the potential of fungi in this region to produce active secondary metabolites, we aim to contribute to the discovery of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 21 publications
(33 reference statements)
2
13
0
3
Order By: Relevance
“…With the exception of Plectosphaerella, all the other genera were also identified in a similar study, which showed the diversity in sea foam-derived fungi on the coast of the Canadian Prince Edward Island [4]. The literature shows that these species are common across a wide array of niches in both terrestrial and marine environments [43][44][45][46]. Similar to previous studies, the majority of sea foam fungal isolates found in this study are ubiquitous saprophytes [1,4].…”
Section: Discussionsupporting
confidence: 87%
“…With the exception of Plectosphaerella, all the other genera were also identified in a similar study, which showed the diversity in sea foam-derived fungi on the coast of the Canadian Prince Edward Island [4]. The literature shows that these species are common across a wide array of niches in both terrestrial and marine environments [43][44][45][46]. Similar to previous studies, the majority of sea foam fungal isolates found in this study are ubiquitous saprophytes [1,4].…”
Section: Discussionsupporting
confidence: 87%
“…Other studies reported the bioactivity of this genus against Xanthomonas (Henríquez et al, 2014), including some from our research group, against X. citri, X. euvesicatoria and X. axonopodis pv. passiflorae (Vieira et al, 2018, but so far no molecules have been described.…”
Section: Discussionmentioning
confidence: 99%
“…New microorganisms and natural products can be isolated from extreme environments, such as Antarctica (Pikuta et al, 2007). Many studies highlight the potential of the Antarctic environment in the production of bioactive metabolites (Furbino et al, 2014), antifungal substances (Svahn et al, 2015) and active compounds against Xanthomonas species, including X. citri (Moncheva et al, 2002;Encheva-Malinova et al, 2015;Puric et al, 2018;Vieira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the species P. appendiculatus , P. destructans , P. pannorum , P. verrucosus , and P. vinaceous have been isolated from different Antarctic environments (Loque et al, 2010; Gomes et al, 2018; Alves et al, 2019; Kochkina et al, 2019; Rosa et al, 2019). Several studies have shown that extracts of these fungi produce bioactive metabolites with potential application, including antibacterial, antifungal, tripanocidal, herbicidal, and antitumoral activities (Furbino et al, 2014; Henríquez et al, 2014; Gonçalves et al, 2015; Gomes et al, 2018; Purić et al, 2018; Vieira et al, 2018). On the other hand, Pseudogymnoascus strains of Antarctic origin also have shown ability to produce cold-adapted enzymes with potential application in several industrial processes (Loperena et al, 2012; Poveda et al, 2018).…”
Section: Introductionmentioning
confidence: 99%